Biomarkers in Diabetic Retinopathy and the Therapeutic Implications - Zorena, Katarzyna; Raczyńska, Dorota; Raczyńska, Krystyna (Mediators of Inflammation, 2013)
The main problem both in type 1 (T1DM) and type 2 (T2DM) diabetes is the development of chronic vascular complications encompassing micro- as well as macrocirculation. Chronic complications lower the quality of life, lead to disability, and are the cause of premature death in DM patients. One of the chronic vascular complications is a diabetic retinopathy (DR) which leads to a complete loss of sight in DM patients. Recent trials show that the primary cause of diabetic retinopathy is retinal neovascularization caused by disequilibrium between pro- and antiangiogenic factors. Gaining knowledge of the mechanisms of action of factors influencing retinal neovascularization as well as the search for new, effective treatment methods, especially in advanced stages of DR, puts special importance on research concentrating on the implementation of biological drugs in DR therapy. At present, it is antivascular endothelial growth factor and antitumor necrosis factor that gain particular significance.